The Dynamics of the French Multiparty System and Its Relation to Multiculturalism - Achadiat, Karina Ayu Triutami; Ibrahim, Bethoven Ferry (Candidate: Jurnal Sains Politik, 2023)
This article will discuss the implementation of the multiparty system in France and the implementation of the French legislative elections in 2022. To discuss these two things, a study of various relevant literature sources was carried out. France is one of the various countries in the world that implements a multi-party system as its party system. This of course makes France a country that applies democratic values in its political life, because the multi-party system is a party system that can be said to provide wide enough opportunities for its citizens to be able to participate in managing their country through political parties based on their respective ideologies. respectively. However, of course, there are strengths and weaknesses in every party system, and the multiparty system is no exception. The strengths are certainly not far from the role of political parties as a forum for people to be able to express their aspirations politically, as well as ideological freedom for each political party. In addition, the wide opportunity for new parties to emerge and participate in contests in the election is also a strength. While the weaknesses are when the executive tends to be weaker to be able to carry out its role in government, this is because no one political party can fully dominate another political party when occupying an executive position so it must form a coalition with other political parties. The multiparty system will also have an influence on the dynamics that occur in the electoral process.